2013
DOI: 10.1111/dme.12322
|View full text |Cite
|
Sign up to set email alerts
|

The optimal morning:evening ratio in total dose of twice‐daily biphasic insulin analogue in poorly controlled Type 2 diabetes: a 24‐week multi‐centre prospective, randomized controlled, open‐labelled clinical study

Abstract: These results indicate that initiating twice-daily biphasic insulin analogue on regimens with a higher dose before breakfast than before dinner (i.e. ratio approximately 55:45 to 60:40) might be more appropriate in Korean subjects with Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Of these #bib165 were duplicates and 356 were excluded. Three additional studies were identified (including two that had been submitted, but not published at the time of the literature search); hence 18 studies from the literature were included in the review. Three eligible studies were identified in the search of ClinicalTrials.gov and included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these #bib165 were duplicates and 356 were excluded. Three additional studies were identified (including two that had been submitted, but not published at the time of the literature search); hence 18 studies from the literature were included in the review. Three eligible studies were identified in the search of ClinicalTrials.gov and included.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (n = 15) [15][16][17][21][22][23]25,27,[29][30][31][32][33][34][35] included patients with a minimum HbA1c of ≥7.0 or ≥7.5% (Table 1). One study 18 included patients on the basis of FPG and postprandial plasma glucose concentrations (≥7 and ≥11.1 mmol/L, respectively).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…These patients were randomly assigned to a long-acting insulin analogue and biphasic insulin analogue, or were switched from OHAs to twice-daily of premixed insulin lispro 25 or premixed insulin aspart protamine 30 121415. All patients were followed up in October 2014 at Severance Diabetes Center, Seoul, South Korea.…”
Section: Methodsmentioning
confidence: 99%
“…A standardized mixed meal (Ensure, Meiji Dairies Corporation, Tokyo, Japan; total 500 kcal, 17.5 g fat, 68.5 g carbohydrate, and 17.5 g protein) stimulation test was conducted after an 8-hour overnight fast, and postprandial glucose and C-peptide were measured at 90 minutes in 33.1% of subjects. In the rest of 66.9% of subjects, postprandial glucose and serum were measured 2 hours after each subject's conventional diet 121415…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation